2021
DOI: 10.4239/wjd.v12.i7.954
|View full text |Cite
|
Sign up to set email alerts
|

Ejaculatory dysfunction in men with diabetes mellitus

Abstract: Diabetes mellitus (DM) is a metabolic disorder that is characterized by elevated blood glucose levels due to absolute or relative insulin deficiency, in the background of β-cell dysfunction, insulin resistance, or both. Such chronic hyperglycemia is linked to long-term damage to blood vessels, nerves, and various organs. Currently, the worldwide burden of DM and its complications is in increase. Male sexual dysfunction is one of the famous complications of DM, including abnormal orgasmic/ejaculatory functions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 161 publications
(196 reference statements)
0
19
0
4
Order By: Relevance
“…This Diabetes mellitus (DM) is a growing metabolic and endocrinological disorder characterised by chronic hyperglycaemia secondary to absolute/relative insulin insufficiency and/or insulin resistance on a background β-cell dysfunction at the pancreatic islets. 1 It has a rapidly rising prevalence in both, developed and developing countries, with more than 422 million people thought to be suffering from the disease globally in 2014. 2 This has almost quadrupled from 108 million in 1980 worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This Diabetes mellitus (DM) is a growing metabolic and endocrinological disorder characterised by chronic hyperglycaemia secondary to absolute/relative insulin insufficiency and/or insulin resistance on a background β-cell dysfunction at the pancreatic islets. 1 It has a rapidly rising prevalence in both, developed and developing countries, with more than 422 million people thought to be suffering from the disease globally in 2014. 2 This has almost quadrupled from 108 million in 1980 worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, DM is a known aetiological factor contributing to EjD. 1,9 Whilst disorders of ejaculation are commonly considered concurrently alongside other aspects of sexual dysfunction (largely ED), in this review, we will focus on the ejaculatory aspect of sexual dysfunction, in particular PE, RE, DE and AE as these are the most common ejaculatory disorders associated with DM. There are multiple pathological mechanisms proposed that can contribute to the aetiology of EjD in DM and a knowledge of these can aid the clinician in understanding the various therapies available for diabetic men with ejaculatory disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Erectile dysfunction (ED) is a disorder that is usually linked to either psychological or organic causes (cardiovascular, neurological and/or endocrine disorders). It was demonstrated that ED is in diabetics has a prevalence odd of about 3.5 times more than in healthy subjects (Kouidrat et al, 2017; Mostafa & Abdel‐Hamid, 2021; Nutalapati et al, 2020). The occurrence of ED in diabetics has been associated with risk factors like advanced age, longer duration, poor glycaemic control, presence of hypertension, dyslipidaemia, smoking, as well as sedentary lifestyle (Bahar et al, 2020; Tamrakar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, even a candidate for assisted reproductive technique (ART), with normal spermatogenesis and no obstruction, can impose a serious challenge for infertility centers; in other words, ejaculation disorder and obtaining the sperm make sperm retrieval a dilemma for the clinicians ( 6 ). There are also important controversies in certain groups about the best method of sperm retrieval ( 7 ). Therefore, in this article, the methods of obtaining sperm in patients with permanent ejaculation disorders are assessed and the appropriate strategy for treatment is commented and explained.…”
Section: Introductionmentioning
confidence: 99%